The Influence of Supply Chain Management, Kaizen Culture on Productivity in the Automotive Industry in Cikarang - Widiyanti Widiyanti; Siti Yulia Salsa Fahrani; Raden Firyal Fadhlin Camila; Marcellawati Cecar; Siti Adrianti (DPPM Universitas Pelita Bangsa, 2024)
In an increasingly competitive industrial environment, companies are required to manage their supply chains effectively while continuously pursuing improvement and innovation. This study aims to analyze the influence of supply chain management and the Kaizen culture on employee productivity. By distributing questionnaires and utilizing Structural Equation Modeling (SEM) for analysis, the research collected data from several automotive companies in Cikarang. The findings reveal that the effective implementation of supply chain management has a positive impact on employee productivity. Furthermore, the Kaizen culture, which emphasizes continuous improvement, also positively influences productivity enhancement. These findings underscore the importance of effective supply chain management and the implementation of a culture of continuous improvement in enhancing employee productivity, thereby maintaining the company's competitiveness in an increasingly challenging industrial landscape.